Author Correction: Identifcation, heterologous production and bioactivity of lentinulin A and dendrothelin A, two natural variants of backbone N-methylated peptide macrocycle omphalotin A - Emmanuel Matabaro (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.